THE IMPACT OF UNIVERSITY PREVENTIVE AWARENESS IN REDUCING THE IMPACT OF ECONOMIC FACTORS LEADING TO THE INCREASE IN THE PHENOMENON OF DRUG ABUSE IN THE UNIVERSITY ENVIRONMENT - Zahraa Saad Sabri (Scholar Express Journals, 2025)
The research aims to identify, test, and understand the impact of economic factors on the spread of drug abuse in the university environment and to understand the role of universities in raising awareness of the dangers of drug abuse through research in a number of private universities in Iraq. This is done by finding a solution to the basic problem formulated with the following question: (Do economic factors affect the increase in drug abuse rates in the university environment, and can universities reduce it through the application of preventive awareness practices?). The research has great importance in drawing attention to the importance of clarifying these economic factors and their impact on drug abuse rates and directing attention to the role that universities can play in raising awareness about the dangers of drugs and reducing the spread of this phenomenon in the university student environment. Despite the generality of the problem of drug abuse and its variables, it has extended beyond young people with a limited and simple educational level to university youth, as its danger lies in the negative effects on the abuser and not only that, but also on societies themselves. Thus, the main hypothesis of the research was formulated, which aims to find both the correlation and the impact of the research variables, namely: (There is a statistically significant moral impact of university awareness on the economic factors leading to an increase in drug abuse in the university environment). To test these hypotheses Field research was adopted, which was applied in a number of governmental and private universities in Baghdad. Data was collected based on a questionnaire form, and the research sample amounted to (380) individuals , male and female students in the universities, the research sample. Statistical methods were adopted, represented by the programs ( EXCEL 2010 ) , ( SPSS V 28 ) , (AMOS V.26) In analyzing this data in order to calculate the coefficient of variation, standard deviation, and correlation coefficient and test the research hypothesis, the research results reached: The respondents' awareness of the seriousness of economic determinants and their prominent role in pushing students towards drug use. The results also showed a general agreement that poverty, unemployment, low family income, and the resulting psychological crises are all direct factors that increase the likelihood of drug use, in addition to their negative repercussions on the national economy and the increase in the illicit wealth of drug dealers .
Keywords: Economic Factors; Drugs; Preventive Awareness